The Combination of Acupressure and Cupping Therapy for Hypertension Patients' Blood Pressure - Sintiya Halisya Pebriani; Lily Marleni; Adi Saputra; Dessy Suswitha; Mardiah; Abbas, Hasriwiani Habo (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Hypertension that is not controlled and occurs in the long term will affect all body organ systems resulting in various complications that can cause death. To prevent complications in hypertension, it is necessary to control hypertension, one of which is by complementary therapy in the form of acupressure and cupping. This study aims to determine differences in blood pressure in patients with hypertension after acupressure therapy combined with cupping therapy with wet cupping therapy. The type of research is Quasy Experiment with pre-post test with a control group design. The study was conducted at the Asy-Syaafi Holistic Center with a sample of 34 hypertension patients where 14 respondents were in the intervention group and 14 respondents in the control group. The data analyst used the Independent T-test. The results found that there was no difference in systolic blood pressure (p-value 0.800) and diastolic (p-value 0.274) between the intervention group and the control group, but there was a significant difference in systolic blood pressure (p-value 0.000) and diastolic (p-value 0.002) in the intervention group. before and after cupping acupressure therapy and there was a difference in systolic (p value 0.000) and diastolic (p value 0.000) blood pressure in the control group before and after wet cupping therapy. it can be concluded that there is no difference in blood pressure between the group given acupressure combination cupping therapy and the group given wet cupping therapy alone.